Psychological well-being and factors affecting it after the COVID-19 pandemic - Towhid Babazadeh; Saber Ghaffari-fam; Farzaneh Shahnavaz-Yoshanluie; Soheila Ranjbaran (Frontiers in Psychology, 2024)
IntroductionThe COVID-19 pandemic has enormously impacted human activity worldwide, partly due to many governments issuing stay-at-home orders and limiting the types of social interactions citizens can engage in. Hence, this study investigated psychological well-being and factors affecting it after the COVID-19 pandemic.MethodsA total of 345 participants were recruited in the study. This research was conducted between February and May 2023 in Sarab, East Azerbaijan, Iran. To measure the data, valid and reliable instruments of Goldberg’s General Health Questionnaire (GHQ-28), Multidimensional Health Locus of Control (MHLC), interpersonal support evaluation list (ISEL-SF), and health-protective behaviors checklist instrument were used.ResultsAccording to the results, health locus of control (r = 0.227; p < 0.001), social support (r = 0.339; p < 0.001), and COVID-19 preventive behaviors (r = 0.376; p < 0.001) were positively correlated with psychological well-being. The strongest correlation was observed between psychological well-being and protective behaviors (r = 0.376; p < 0.001). In the hierarchical regression model, total, demographic characteristics along with health locus of control, social support, covid-19 preventive behaviors, and history of COVID-19 infection were able to explain 57.4% of the variation in psychological well-being.DiscussionPublic healthcare providers’ and policymakers’ preventive and supportive actions are highly advised for promoting health locus of control and social support in adults after the COVID-19 pandemic. In addition, it is better to include a community’s social and environmental changes.